Lithuanian boyairs attitude towards the reforms of the Four years diet (in accordance with the directions of local diets) - Egidijus Raila (Lietuvos Istorijos Studijos)
The political and economical destruction in the Commonwealth was beginning to increase during the second part of the eighteenth century. The rather vague activity of the political structures was not able to restrain the arrogance of the boyars. On the other hand, the boyars themselves were not very keen on sacrificing their own interests for the sake of a strong centralized authority.